Thermal analysis characterization of PAAm-co-MC hydrogels - Gabbay Alves, Tais Vanessa; Madureira Tavares, Eraldo Jose; Aouada, Fauze Ahmad [UNESP]; Brito Negrao, Charles Alberto; Chaves Oliveira, Marcos Ene [UNESP]; Duarte Junior, Anivaldo Pereira; Ferreira da Costa, Carlos Emmerson; Carrera Silva Junior, Jose Otavio; Ribeiro Costa, Roseane Maria (Springer, 2011)
This paper reports the thermal characterization of polyacrylamide-co-methylcellulose hydrogels and the constituent monomers (acrylamide and methylcellulose). Polymeric materials can be used to produce hydrogels, which can be natural, synthetic, or a mixture. The hydrogels described here were obtained by free radical polymerization, in the presence of N,N'-methylene-bis-acrylamide as a cross-linker agent. Four acrylamide concentrations were used for the synthesis of hydrogels: 3.6, 7.2, 14.7, and 21.7% (w/v). The materials so obtained were analyzed by TG, DTG, DSC, and FT-IR. The TG curves of acrylamide and methylcellulose showed three mass loss events. In DSC curves, the acrylamide exhibited one melting peak at 84.5 A degrees C, and methylcellulose indicated one exothermic event. Nevertheless, acrylamide was considered more stable than methylcellulose. The TG curves of the hydrogels exhibited three mass loss events, and on the DSC curves, three endothermic events were observed. It was verified that the different acrylamide proportions influenced the thermic behavior of hydrogels, and that the authors considered the 7.2% hydrogel a promising drug carrier system. The absorption bands were well defined, confirming the presence of the functional groups in the samples.
Keywords: Hydrogels; Polymers; Thermal analysis; PAAm-co-MC